A new reformation : from Luther's world to ours - Fuquay, Rob (Nashville : Abingdon Press, 2018)
Discover what makes Martin Luther's message revolutionary today!
Cover; Title; Copyright; Dedication; Contents; Introduction; 1. A Perfect Storm; 2. Sola Scriptura; 3. Sola Fide; 4. Taking a Stand; 5. Refuge; 6. The Priesthood of All Believers; Afterword; Acknowledgments; Notes
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072, 600, 650 - OCLC control number change
Keywords: Luther, Martin, -- 1483-1546.; Luther, Martin, -- 1483-1546.; Reformation; Church renewal; Christian life; Christian life; Church renewal; Reformation; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books